2021
DOI: 10.1128/aem.02238-20
|View full text |Cite
|
Sign up to set email alerts
|

A Major Facilitator Superfamily (MFS) Efflux Pump, SCO4121, from Streptomyces coelicolor with Roles in Multidrug Resistance and Oxidative Stress Tolerance and Its Regulation by a MarR Regulator

Abstract: Overexpression of efflux pumps is one of the major determinants of resistance in bacteria. Streptomyces harbor a large array of efflux pumps that are transcriptionally silenced under laboratory conditions. However, their dissemination results in multidrug resistance in different clinical pathogens. In this study, we have identified an efflux pump from Streptomyces coelicolor, SCO4121, belonging to the MFS family of transporters and characterized its role in antibiotic resistance. SCO4121, provided resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 89 publications
0
35
0
Order By: Relevance
“…The second most common synonymous variant was another A to G change in PA3709 encoding Ala 340 of a probable major facilitator superfamily (MFS) transporter protein. Overexpression of efflux pumps that include MFS transporters are associated with increased resistance to antibiotics [15, 40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most common synonymous variant was another A to G change in PA3709 encoding Ala 340 of a probable major facilitator superfamily (MFS) transporter protein. Overexpression of efflux pumps that include MFS transporters are associated with increased resistance to antibiotics [15, 40].…”
Section: Resultsmentioning
confidence: 99%
“…The second most common synonymous variant was another A to G change in PA3709 encoding Ala 340 of a probable major facilitator superfamily (MFS) transporter protein. Overexpression of efflux pumps that include MFS transporters are associated with increased resistance to antibiotics [14,39]. Despite none of the pairwise effects having known interactions, the majority variants identified are very poorly characterised so the possibility of a true combined effect of Ciprofloxacin resistance cannot be ruled out.…”
Section: Antibacterial Resistancementioning
confidence: 99%
“…Our results demonstrated that there were mutations in multiple transcriptional genes (MarR family transcriptional regulator, TetR family transcriptional regulator, and MerR family transcriptional regulator). At present, MarR family transcriptional regulator and TetR family transcriptional regulator were found that closely related to bacterial oxidative stress, biofilm formation, and drug resistance by regulating the efflux pump and signal transduction (Colclough et al, 2019;Fritsch et al, 2019;Nag and Mehra, 2021;Van Loi et al, 2021). Licochalcone A may have multiple target genes in E. faecalis, for instance, the MarR family transcriptional regulator and TetR family transcriptional regulator may be the target genes of licochalcone A in E. faecalis in this study, which lead to licochalcone A and has a high drug resistance barrier to E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…( Grove, 2013 ). In spite of abundant distribution of MFRs in the antibiotic-producing actinomycetes, just a few members have been characterized in Streptomyces ( Yang et al, 2010 ; Davis et al, 2013 ; Huang and Grove, 2013 ; Zhang et al, 2015 ; Guo et al, 2018 ; Kong et al, 2019 ; Nag and Mehra, 2021 ), and the functional probe into MFRs in Sac. erythraea has not been reported.…”
Section: Discussionmentioning
confidence: 99%